1997
DOI: 10.1002/apj.5500050308
|View full text |Cite
|
Sign up to set email alerts
|

A Revised Analysis of the Effect of Surfactants on Two‐Phase Phenomena in Horizontal Air‐Water Pipe Flow

Abstract: Flow regimes, hold-up and pressure loss measurements in two-phase air-water co

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The gravitational waves observed in Region I, when tap water is used, disappear when a small quantity of the surfactant Tween R is added to the water. This observation is in agreement with the remarks of Spedding and Hand [11], who report that the small amplitude gravitational waves on the liquid surface are suppressed due to the addition of the surfactant. Region II is observed for all the liquids employed.…”
Section: Liquid Layer Characteristicssupporting
confidence: 93%
See 2 more Smart Citations
“…The gravitational waves observed in Region I, when tap water is used, disappear when a small quantity of the surfactant Tween R is added to the water. This observation is in agreement with the remarks of Spedding and Hand [11], who report that the small amplitude gravitational waves on the liquid surface are suppressed due to the addition of the surfactant. Region II is observed for all the liquids employed.…”
Section: Liquid Layer Characteristicssupporting
confidence: 93%
“…Spedding and Hand [11] and Soleimani et al [12] have also observed that the addition of very small quantities of polymers in water results in both a significant increase of the liquid hold up (up to 30% compared to that of pure water) and the reduction of the wave amplitude (i.e., h rms ), despite the reduced surface tension. Several researchers [11,12] attribute this fact either to an increased surface viscosity or to the turbulence damping at the liquid in- terface. In summary, the smooth-to-wavy flow transition Re L for the surfactant solution is smaller than that for the water and glycerin solutions.…”
Section: Liquid Layer Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Polymers were utilized in many occasions as DRAs in gas-liquid and liquid-liquid flow systems [52][53][54][55][56][57][58][59]. Compared to polymer DRAs, surfactant DRAs attracted less attention and have been mainly applied in gas-liquid flow systems [60][61][62][63]. Al-Sarkhi and Soleimani [64], investigated the effect of applying polymeric DRA in gas-liquid system flowing through horizontal pipelines.…”
mentioning
confidence: 99%
“…Spedding and Hand (1997) in a review paper summarized the studies that examine the effect of surfactant additives on two-phase pipe-flow. Wilkens and Thomas (2007) performed two-phase pressure drop measurements for air/water mixtures in a 0.052 m diameter horizontal pipe and they found that the addition of 400 ppm of SDS to the water reduced the pressure drop by 25-40% compared to the same flow rates of water.…”
Section: Introductionmentioning
confidence: 99%